Factors associated with suboptimal intake of some important nutrients among HIV-positive pregnant adolescents from two Ghanaian districts - Laar, A.K.; Ampofo, W.K.; Tuakli, J.M.; Wonodi, C.; Asante, R.K.; Quakyi, I.A. (Journal of the Ghana Science Association, 2009)
This study determined the daily intakes of some important nutrients and factors associated with the suboptimal intakes of these nutrients among young HIV-positive (HIV+) pregnant women from two Ghanaian districts. Eighty-jive of such women after informed consent were recruited from three hospitals and were interviewed using a structured questionnaire. Dietary intake was quantified using the 24-hour recall technique. Total intake, calculated based on dietary recall, and adequacy of intake, calculated based on intake levels compared to the RDA, were assessed. Factors potentially associated with intake were tested using the Mann Whitney U test. The median daily intakes of the nutrients of interest were as follows: Protein (63.1 g), Vitamin C (106 mg), Zinc (11.7 mg), Iron (22.2 mg), and Selenium (1.4 micrograms). The prevalence of inadequacy of these nutrients were: Vitamin C (35.3%), Protein (39.7%), Iron (72.9%), Selenium (97.6%), and Zinc (100%). HIV + women with nausea, vomiting, and oral lesions had significantly lower intakes of Protein, Iron and Zinc (p < 0.05). Inadequacy of dietary intake is very prevalent among this group of pregnant women particularly among those with nausea, vomiting, and oral lesions. These conditions could be significant contributors to the burden of nutrient deficiencies among women infected with HIV in this setting. Since deficiencies of these nutrients during pregnancy could lead to adverse pregnancy outcomes, emphasis on the dietary sources of these nutrients such as fish, peas, nuts, kontomire, whole grain cereals, seafood, onions, milk, garlic, alfalfa, mushrooms, and banana should be made during antenatal counseling.
Keywords: HIV; pregnant adolescent; suboptimal intake; nutrients; Ghana